Bad Kitty: Supercat (Graphic Novel) - Bruel, Nick (New York : Roaring Brook Press, 2022)
It's been a long time since Kitty has had a play date. So, her owners decide it's about time she interacts with some friends. But the play date takes a turn when Kitty and her friend, Strange Kitty, don their armor and become...Super Cat and Captain FantastiCat! Together, they must go on a scavenger hunt across the world (their house and yard) and recover the Orbs of Destiny (some dog balls) in order to prevent the 92 universes from being turned into cheese by the nefarious Dr. Lagomorph. Will they succeed in their mission? Or will the world as we know it descend into chaos and curds?
Keywords: Friendship -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Cats; Graphic novels; Comics (Graphic works); Graphic novels